Linear scanning method based on the SAFT coarray - Martín, C. J.; Martínez-Graullera, O.; Romero, D.; Higuti, R. T. [UNESP]; Ullate, L. G. (AIP Publishing, 2010)
This work presents a method to obtain B-scan images based on linear array scanning and 2R-SAFT. Using this technique some advantages are obtained: the ultrasonic system is very simple; it avoids the grating lobes formation, characteristic in conventional SAFT; and subaperture size and focussing lens (to compensate emission-reception) can be adapted dynamically to every image point. The proposed method has been experimentally tested in the inspection of CFRP samples. © 2010 American Institute of Physics.
Keywords: Linear array; SAFT; Ultrasonic NDE